Interaction proteome of human Hippo signaling: modular control of the co‐activator YAP1. Issue 1 (20th December 2013) - Hauri, Simon; Wepf, Alexander; van Drogen, Audrey; Varjosalo, Markku; Tapon, Nic; Aebersold, Ruedi; Gstaiger, Matthias
Abstract: Tissue homeostasis is controlled by signaling systems that coordinate cell proliferation, cell growth and cell shape upon changes in the cellular environment. Deregulation of these processes is associated with human cancer and can occur at multiple levels of the underlying signaling systems. To gain an integrated view on signaling modules controlling tissue growth, we analyzed the interaction proteome of the human Hippo pathway, an established growth regulatory signaling system. The resulting high‐resolution network model of 480 protein‐protein interactions among 270 network components suggests participation of Hippo pathway components in three distinct modules that all converge on the transcriptional co‐activator YAP1. One of the modules corresponds to the canonical Hippo kinase cassette whereas the other two both contain Hippo components in complexes with cell polarity proteins. Quantitative proteomic data suggests that complex formation with cell polarity proteins is dynamic and depends on the integrity of cell‐cell contacts. Collectively, our systematic analysis greatly enhances our insights into the biochemical landscape underlying human Hippo signaling and emphasizes multifaceted roles of cell polarity complexes in Hippo‐mediated tissue growth control. Synopsis: Systematic characterization of the human Hippo pathway protein interactome by quantitative mass spectrometry generates a high‐resolution network of 480 interactions among 270 proteins and reveals three major modules linked to the transcriptional coactivator YAP1. The interactome of human Hippo signaling provides a rich resource of high confidence protein interactions. Network topology revealed three major modules containing phosphatases, kinases and cell polarity proteins and converging at the transcriptional coactivator YAP1. A subset of protein phosphatase 1 complexes binds and activates YAP1. Cell‐cell contacts control YAP1 transcriptional activity as well as YAP1 complex formation with proteins linked to cell polarity. Abstract : Systematic characterization of the human Hippo pathway protein interactome by quantitative mass spectrometry generates a high‐resolution network of 480 interactions among 270 proteins and reveals three major modules linked to the transcriptional coactivator YAP1.